2014
DOI: 10.3345/kjp.2014.57.11.484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenotonsillar hypertrophy on right ventricle function in children

Abstract: PurposeChronic upper airway obstruction causes hypoxemic pulmonary vasoconstriction, which may lead to right ventricle (RV) dysfunction. Adenotonsillar hypertrophy (ATH) is the most common cause of upper airway obstruction in children. Therefore, we aimed to evaluate RV function in children with ATH.MethodsTwenty-one children (male/female, 15/6; mean age, 92.3¡¾39.0 months; age range, 4-15 years) with ATH and 21 healthy age- and gender-matched controls were included in this study. Tricuspid annular plane systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…10 Severe forms of obstructive sleep apnoea due to adenotonsillar hypertrophy may be complicated by pneumonia, cor pulmonale, pulmonary hypertension, chronic hypercapnia or hypoxia and right heart failure. [11][12][13] However, adenotonsillar hypertrophy has been reported to more commonly cause acute and chronic otitis media, rhinosinusitis, maldevelopment of upper jaw and poor physical and mental development due to chronic hypoxia. 14 For proper assessment, good history of presenting symptoms such as mouth, breathing, noisy breathing, snoring, frequent awake from sleep, enuresis, nightmares, hypersomnolence, feeding habit and academic performance must be taken.…”
Section: Introductionmentioning
confidence: 99%
“…10 Severe forms of obstructive sleep apnoea due to adenotonsillar hypertrophy may be complicated by pneumonia, cor pulmonale, pulmonary hypertension, chronic hypercapnia or hypoxia and right heart failure. [11][12][13] However, adenotonsillar hypertrophy has been reported to more commonly cause acute and chronic otitis media, rhinosinusitis, maldevelopment of upper jaw and poor physical and mental development due to chronic hypoxia. 14 For proper assessment, good history of presenting symptoms such as mouth, breathing, noisy breathing, snoring, frequent awake from sleep, enuresis, nightmares, hypersomnolence, feeding habit and academic performance must be taken.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, exclusion of the patients having diseases such as heart and renal failure, severe lung disease, or upper airway obstruction caused by other reasons like nasal polyps, which are likely to influence NT-proBNP levels, allowed elimination of confounding factors. In their study, Lee et al (11) reported that, children with ATH (n=21) who had no echocardiographic right ventricular dysfunction and had similar echocardiographic parameters with the control group (n=21), had significantly higher NTproBNP levels than the controls (66.44±37.63 pg/mL vs. 27.85±8.89 pg/mL, p=0.001). In their study on 90 children with OSAS and age-and gender-matched controls (n=45), Goldbart et al (12) reported higher NT-proBNP levels in OSAS children than in the controls (189.1±112.7 pg/mL vs. 104.8±49.5 pg/mL, p=0.006).…”
Section: Discussionmentioning
confidence: 99%
“…Upper airway obstruction in children is most commonly caused by adenotonsillar hypertrophy (AH) . The AH condition also contributes to the development of obstructive sleep apnea (OSA) , leading to significantly lower quality of life from neurocognitive , behavioral , and cardiovascular concerns.…”
Section: Introductionmentioning
confidence: 99%
“…The AH condition also contributes to the development of obstructive sleep apnea (OSA) , leading to significantly lower quality of life from neurocognitive , behavioral , and cardiovascular concerns. Adenotonsillectomy (AT; the surgical removal of the adenoids and tonsils) is commonly used to treat AH and AH‐related sleep disorders , but guidelines are lacking to aid surgical decision‐making . While patient‐reported improvement following surgery is between 70% and 80%, persistent symptoms of sleep‐related breathing disorders have been reported in as many as 25% of normal‐weight and 75% of obese children after surgical management .…”
Section: Introductionmentioning
confidence: 99%